2020
DOI: 10.1073/pnas.2008535117
|View full text |Cite
|
Sign up to set email alerts
|

Tight and specific lanthanide binding in a de novo TIM barrel with a large internal cavity designed by symmetric domain fusion

Abstract: De novo protein design has succeeded in generating a large variety of globular proteins, but the construction of protein scaffolds with cavities that could accommodate large signaling molecules, cofactors, and substrates remains an outstanding challenge. The long, often flexible loops that form such cavities in many natural proteins are difficult to precisely program and thus challenging for computational protein design. Here we describe an alternative approach to this problem. We fused two stable proteins wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…These data can now be used to accelerate the development of future custom design protein stability curves which, in turn, will expand the biomedical and biotechnological applications of de novo proteins. For example, by fusion to another de novo protein, one of the stabilized scaffolds reported here (DeNovoTIM13) has been successfully used to create a reaction chamber on the top of the barrel, 58 confirming the convenience of working with robust and stable TIM barrels in the path towards functional de novo proteins.…”
Section: Discussionsupporting
confidence: 54%
“…These data can now be used to accelerate the development of future custom design protein stability curves which, in turn, will expand the biomedical and biotechnological applications of de novo proteins. For example, by fusion to another de novo protein, one of the stabilized scaffolds reported here (DeNovoTIM13) has been successfully used to create a reaction chamber on the top of the barrel, 58 confirming the convenience of working with robust and stable TIM barrels in the path towards functional de novo proteins.…”
Section: Discussionsupporting
confidence: 54%
“…Sequence overlap between TIM-barrel subunits for model TIM-barrel designs (orange) and previously characterized sequences for the same scaffold (blue), including sTIM-11 (5bvl, S11) [40], DeNovoTIM15 (6wvs, D15) [44], and NovoTIMs (N6, N13, N14a, N14b) [45]. Specific overlaps shown for the region between ( A ) the helices and the barrel, ( B ) the inner part of the barrel, ( C ) exposed regions, and ( D ) all residues.…”
Section: Supplementary Textmentioning
confidence: 99%
“…( B ) Distribution of rotamer automorphic RMSDs (Å) between crystal structure and template backbone for core and solvent-exposed residues for (top) F2C and (bottom) F15C. ( C ) Sequence overlap between TIM-barrel subunits for model TIM-barrel designs (orange) and previously characterized sequences for the same scaffold (blue), including sTIM-11 (5bvl, S11) [40], DeNovoTIM15 ( 6wvs , D15) [44], and NovoTIMs (N6, N13, N14a, N14b) [45]. Edge thickness increases with overlap.…”
mentioning
confidence: 99%
“…Structural and folding analysis showed that epistatic effects allow navigating an unexplored region of the stability landscape of natural proteins. One of these DeNovoTIMs was already used in a successful recombination with a de novo designed ferredoxin protein and engineered to bind lanthanide [ 87 ]. In another recent study, Wiese et al extended sTIM11 by successfully incorporating a rationally designed small α-helix into a βα loop [ 88 ].…”
Section: Learning From Nature Towards Protein Designmentioning
confidence: 99%